Orthotropic energy-absorbing metamaterial, preparation method and application

By using orthogonal anisotropic structure and alternate layered fill polyurethane and epoxy resins in energy-absorbing metamaterials, the problems of single energy absorption mechanism and low energy absorption efficiency of existing energy absorption metamaterials are solved, and more efficient energy absorption and a wider energy absorption range are achieved, reducing process complexity and cost.

CN119708824APending Publication Date: 2025-03-28BEIJING UNIV OF CIVIL ENG & ARCHITECTURE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411986388.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing energy absorption metamaterial has a single energy absorption mechanism, low energy absorption efficiency, limited energy absorption range, and complex preparation process and high cost, which limits its popularity in large-scale applications.

Method used

The energy-absorbing metamaterial with orthogonal anisotropic structure is composed of an open-cell foam metal matrix and alternately layered polyurethane and epoxy resin. The polymer curing time is reasonably controlled, and the good layering effect between different polymers is achieved.

Benefits of technology

It improves the energy absorption efficiency and energy absorption range of the material, reduces process complexity and cost, and meets the energy absorption characteristics requirements in different directions, and has a wide practical application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708824A_ABST
    Figure CN119708824A_ABST
Patent Text Reader

Abstract

The invention provides an orthotropic energy-absorbing metamaterial, a preparation method and application, an open-cell foam metal matrix is alternately filled with two polymers of polyurethane and epoxy resin in a layered manner, and good plasticity of a foam metal-polyurethane (AF-PU) material and high strength of a foam metal-epoxy resin (AF-EP) material are combined, so that the orthotropic energy-absorbing metamaterial is obtained. The orthotropic energy-absorbing metamaterial is formed, so that different polymers as well as the polymers and the foam metal matrix are mutually coordinated and improved; under the action of external force, respective energy absorption characteristics of different component materials can be fully exerted, so that a good synergistic effect is formed among the component materials, and the overall energy absorption efficiency of the material is also improved while the energy absorption of the material is further enhanced. Meanwhile, the energy-absorbing metamaterial has orthotropic property, has different energy-absorbing characteristics in different directions, and can more widely meet the requirements on energy-absorbing materials in actual engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy absorbing materials and preparation technology, and in particular to an orthotropic energy absorbing metamaterial, a preparation method and application thereof. Background Art

[0002] Energy-absorbing materials are a new type of material with broad application prospects. They have high strength, deformation capacity and energy absorption capacity. When subjected to external forces such as collision, impact and vibration, they can convert external energy into heat energy or other forms of energy through plastic deformation, fracture, friction and other mechanisms inside the material, thereby reducing the degree of damage to the structure caused by external forces and protecting people's lives and property. According to the structure and properties of the material, the commonly used energy-absorbing materials can be divided into several types, such as metals, polymers, ceramics, foam materials and composite materials. Due to its excellent energy absorption performance, it is often widely used in aerospace, transportation, building structures and other fields.

[0003] As one of the indispensable and important materials in passive control technology of structural vibration and structural protection, energy-absorbing metamaterials play a vital role in the control of structural vibration and structural protection. However, the existing energy-absorbing metamaterials have a relatively simple energy absorption mechanism, low energy absorption efficiency, limited energy absorption range, and complex preparation process, high cost, and great limitations in practical engineering applications, which restricts their popularity in large-scale applications. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides an orthotropic energy absorbing metamaterial, a preparation method and an application thereof. The specific contents of the invention are as follows: In a first aspect, the present invention provides an orthotropic energy-absorbing metamaterial, which is composed of an open-pored foam metal matrix, and polyurethane and epoxy resin filled in the cell cavities inside the foam metal matrix; wherein the polyurethane and epoxy resin are alternately layered and filled in the cell cavities inside the foam metal matrix.

[0005] Optionally, the porosity of the foam metal matrix is ​​45-75%, and the pore size of the cell cavity is 5-15 mm.

[0006] Optionally, a single-layer filling height of the polyurethane is the same as a single-layer filling height of the epoxy resin.

[0007] Optionally, the polyurethane and epoxy resin are alternately layered and filled in the cell cavity inside the foam metal matrix, including: the polyurethane is filled in the odd-numbered layers, and the epoxy resin is filled in the even-numbered layers; or the polyurethane is filled in the even-numbered layers, and the epoxy resin is filled in the odd-numbered layers.

[0008] Optionally, the foam metal matrix is ​​a foam aluminum matrix, a foam aluminum alloy matrix or a foam titanium matrix.

[0009] In a second aspect, the present invention provides a method for preparing the orthotropic energy-absorbing metamaterial according to the first aspect, the preparation method comprising: Step 1: placing the foam metal matrix at the center of a large mold with a sealable movable bottom; Step 2, slowly pouring polyurethane or epoxy resin along the gaps around the large mold to the bottom of the mold, and allowing the polyurethane or epoxy resin to fully enter the cell cavity inside the foam metal matrix, and stopping the pouring when the pouring reaches a first predetermined height, and initially solidifying to form a first pouring layer; Step 3, slowly pouring epoxy resin or polyurethane along the gaps around the large mold onto the surface of the first pouring layer, and allowing the epoxy resin or polyurethane to fully enter the cell cavity inside the foam metal matrix, and stopping the pouring when the pouring reaches a second predetermined height, and initially solidifying to form a second pouring layer; Step 4, repeating steps 2 and 3 until the total height of the pouring is consistent with the height of the foam metal matrix, then stopping the pouring and standing to solidify for 1-2 hours; Step 5, inserting the small mold with a movable bottom into the large mold upside down, and making the small mold completely wrap the foam metal matrix, after the whole is inverted, removing the movable bottom of the large mold, and using a demolding tool to press the foam metal matrix into the bottom of the small mold to separate it from the large mold; Step 6: Place the separated small mold in a 50-70° C. constant temperature box for curing for 3-5 hours and then demould to obtain the orthotropic energy-absorbing metamaterial.

[0010] Optionally, the polyurethane is mixed with a first component and a second component, wherein the first component includes: isocyanate; The second component includes: a combined polyether; The curing time required for the pouring layer formed by pouring polyurethane is 3-10 minutes.

[0011] Optionally, the epoxy resin is mixed with a third component and a fourth component, and the third component includes: E44 epoxy resin glue; The fourth component includes: 650 epoxy curing agent; The curing time required for the pouring layer formed by pouring epoxy resin is 5-15 minutes.

[0012] Optionally, the foam metal substrate is first subjected to alkali washing and acid washing before use; Before use, the large mold and the small mold are evenly coated with a release agent on the inner surface.

[0013] In a third aspect, the present invention provides an application of the orthotropic energy-absorbing metamaterial described in the first aspect, wherein the energy-absorbing metamaterial is used as a vertical force-bearing member, a horizontal force-bearing member, and a compressive web member in a building structure.

[0014] Compared with the prior art, the present invention has the following advantages: The present invention provides an orthotropic energy-absorbing metamaterial, which is formed by alternately filling two polymers, polyurethane and epoxy resin, into an open-cell foam metal matrix in layers, combining the good plasticity of foam metal-polyurethane (AF-PU) material with the high strength characteristics of foam metal-epoxy resin (AF-EP) material, so that different polymers and polymers and foam metal matrix can coordinate and improve each other; under the action of external force, the energy absorption characteristics of different component materials can be fully exerted, so that good synergy can be formed between them, and the energy absorption efficiency of the material as a whole is improved while further enhancing the energy absorption of the material. At the same time, the energy-absorbing metamaterial has orthotropic anisotropy and has different energy absorption characteristics in different directions, which can more widely meet the requirements for energy-absorbing materials in practical engineering.

[0015] The present invention also provides a method for preparing an orthotropic energy-absorbing metamaterial, which prepares an orthotropic energy-absorbing metamaterial composed of foam metal and different laminated polymers through a double-mold conversion filling method; and by reasonably controlling the curing time of different polymers at different stages, a good stratification effect between different polymers is achieved. The energy absorption effect is good, the energy absorption category is wide, and the process is simple, the method is concise, and the cost is low, which has important application value in practical engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 A schematic diagram of the three-dimensional structure of a metal substrate provided by an embodiment of the present invention is shown; Figure 2 A schematic diagram of a three-dimensional structure of an orthotropic energy-absorbing metamaterial provided by an embodiment of the present invention is shown; Figure 3 A flow chart of a method for preparing an orthotropic energy-absorbing metamaterial provided by an embodiment of the present invention is shown; Figure 4A schematic structural diagram of a large mold provided by an embodiment of the present invention is shown; Figure 5 A schematic diagram of the structure of a small mold provided by an embodiment of the present invention is shown; Figure 6 A physical picture of the orthotropic energy-absorbing metamaterial provided by the present invention is shown; Figure 7 The stress-strain curves of different energy absorbing materials in the present invention after averaging are shown; Figure 8 A comparison diagram of the ideal energy absorption efficiency of different energy absorption materials in the present invention is shown; Fig. 9 A comparison chart of energy absorption indexes of different energy absorbing materials in the present invention is shown; Fig.10 A schematic diagram of an application of the orthotropic energy-absorbing metamaterial provided by the present invention is shown; Fig.11 Another application schematic diagram of the orthotropic energy-absorbing metamaterial provided by the present invention is shown; Fig.12 Another application schematic diagram of the orthotropic energy-absorbing metamaterial provided by the present invention is shown; Fig.13 Another application schematic diagram of the orthotropic energy-absorbing metamaterial provided by the present invention is shown; Fig.14 Another application schematic diagram of the orthotropic energy-absorbing metamaterial provided by the present invention is shown.

[0018] Description of reference numerals: 1. Foam metal matrix; 2. Cell cavity; 3. Circular through hole; 2-1. Odd-numbered layers; 2-2. Even-numbered layers; 101. Orthotropic energy-absorbing metamaterial; 102. Concrete component; 103. Steel structure component; 1031. Steel plate component; 1032. Steel pipe component; 11. Compression web member of composite structure. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means a limitation on the present invention and its application or use. Based on the embodiments of the present invention, any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts falls within the scope of protection of the present invention. In addition, all other embodiments obtained by ordinary technicians in this field without carrying out creative work belong to the scope of protection of the present invention.

[0020] In the embodiment, no specific experimental steps or conditions are indicated, and the operation or conditions of the conventional experimental steps described in the prior art in this field can be carried out. The reagents used and other instruments that do not indicate the manufacturer are conventional reagent products that can be obtained commercially. In addition, the accompanying drawings are only schematic diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.

[0021] Technologies, methods, and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the description of the present invention.

[0022] In the description of the present invention, it should be understood that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.

[0023] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0024] Before describing in detail the orthotropic energy absorbing metamaterial, preparation method and application provided by the present invention, it is necessary to describe the related technologies as follows: As an existing energy-absorbing material, the aluminum foam-polyurethane composite material has both the light weight and high strength characteristics of aluminum foam and the high damping characteristics of polyurethane viscoelastic materials. Through the combination of the two phases, the composite material has a longer and more stable plastic development platform, and has higher energy absorption capacity and deformation recovery ability. However, the overall yield strength of the composite material is still relatively low, the total energy absorption is low, and the energy absorption mechanism is relatively simple, with great limitations; based on this, the present invention provides an orthotropic energy-absorbing metamaterial and a preparation method thereof. Compared with traditional composite energy-absorbing materials, especially foam aluminum-polyurethane (AF-PU), the energy-absorbing metamaterial provided by the present invention combines the good plasticity of the foam aluminum-polyurethane (AF-PU) material and the high strength characteristics of the foam aluminum-epoxy resin (AF-EP) material by filling the two polymers of polyurethane and epoxy resin into the open-cell foam aluminum matrix in layers and in sequence, so that different polymers and polymers and the foam aluminum matrix can coordinate and improve each other, and the energy absorption characteristics of different component materials can be fully utilized under the action of external forces, and a good synergistic effect is formed between the three, which further enhances the energy absorption of the material while also improving the overall energy absorption efficiency of the material. The specific implementation content is as follows: In a first aspect, the present invention provides an orthotropic energy absorbing metamaterial, which is composed of an open-pore foam metal matrix, and polyurethane and epoxy resin filled in the open pores inside the foam metal matrix; Figure 1 The schematic diagram of the three-dimensional structure of the foam metal matrix provided by the embodiment of the present invention is shown in FIG. Figure 1 The foam metal matrix 1 is composed of a large number of cell cavities 2 and pore walls between the cavities which are closely arranged in three-dimensional directions. The pore walls have different thicknesses and cell cavities of different sizes at different spatial positions, and there is a circular through hole 3 between each two adjacent cavity walls, thereby forming an open-pore foam metal matrix. The foam metal matrix 1 has a honeycomb structure as a whole. The open porosity of the foam metal matrix is ​​45-75%, and the aperture of the open hole is 5-15 mm.

[0025] Figure 2 The schematic diagram of the three-dimensional structure of the orthotropic energy absorbing metamaterial provided by the embodiment of the present invention is shown. Figure 1 and Figure 2 It is found that the orthotropic energy-absorbing metamaterial is composed of a foam metal matrix structure and a structure formed by polyurethane and epoxy resin filled in layers. It should be noted that the number of layers of polyurethane and epoxy resin filled in layers can be controlled within 3-5 layers according to actual use needs; as an example, if the number of layers of layered filling is 3, it can be a layered filling method of polyurethane-epoxy resin-polyurethane, or a layered filling method of epoxy resin-polyurethane-epoxy resin.

[0026] See also Figure 2 , polyurethane and epoxy resin are filled in layers alternately, occupying the cell cavities 2 and circular through holes 3 of different layers of the foam metal matrix; wherein the filling height of a single layer of polyurethane is the same as the filling height of a single layer of epoxy resin. As an example, when filling, polyurethane can be filled in odd-numbered layers 2-1, such as layers 1 and 3, and epoxy resin can be filled in even-numbered layers 2-2, such as layer 2; similarly, epoxy resin can be filled in odd-numbered layers 2-1, such as layers 1 and 3, and polyurethane can be filled in even-numbered layers 2-2, such as layer 2.

[0027] The present invention changes the energy absorption effect of the energy absorption metamaterial by changing the foam metal matrix material, matrix porosity, pore size, etc.; the overall energy absorption capacity of the energy absorption metamaterial can also be changed by changing the thickness, direction, and stacking sequence of the polyurethane layer and the epoxy resin layer inside the matrix; in some embodiments, different foam metal matrices can be selected according to specific usage scenarios, and the foam metal matrix can be a foam aluminum matrix, a foam aluminum alloy matrix, or a foam titanium matrix.

[0028] In a second aspect, the present invention provides a method for preparing the orthotropic energy absorbing metamaterial according to the first aspect. Figure 3 FIG. 4 shows a flow chart of a method for preparing an orthotropic energy absorbing metamaterial provided by an embodiment of the present invention. Figure 3 As shown, the preparation method comprises the following steps: Step 1: Place the foam metal matrix in the large mold so that it is located at the center of the sealable movable bottom of the large mold; Step 2, slowly pouring polyurethane or epoxy resin along the gaps around the large mold to the bottom of the mold, and allowing the polyurethane or epoxy resin to fully enter the foam metal matrix, and stopping the pouring when the pouring reaches a first predetermined height, and initially solidifying to form a first pouring layer; Step 3, slowly pouring epoxy resin or polyurethane along the gaps around the large mold onto the surface of the first pouring layer, and allowing the epoxy resin or polyurethane to fully enter the interior of the foam metal matrix, and stopping pouring when the pouring reaches a second predetermined height, and initially solidifying to form a second pouring layer; Step 4, repeating steps 2 and 3 until the total height of the pouring is consistent with the height of the foam metal matrix, then stopping the pouring and standing to solidify for 1-2 hours; Step 5, inserting the small mold with a movable bottom into the large mold upside down, and making the small mold completely wrap the foam metal matrix, after the whole is inverted, removing the movable bottom of the large mold, and using a demolding tool to press the foam metal matrix into the bottom of the small mold to separate it from the large mold; Step 6, placing the separated small mold in a 50-70° C. constant temperature box for curing for 3-5 hours and then demoulding to obtain the orthotropic energy-absorbing metamaterial; Figure 4 FIG. 1 shows a schematic diagram of the structure of a large mold provided by an embodiment of the present invention; Figure 4 As shown, the bottom of the large mold has an opening, which can be sealed by a sealable movable bottom. Figure 5 FIG. 1 shows a schematic diagram of the structure of a small mold provided by an embodiment of the present invention; Figure 5 As shown, the bottom of the small mold also has an opening, and the components of the small mold also include a gasket with the same size as the bottom area of ​​the small mold; the inner diameter of the large mold is larger than the inner diameter of the small mold. This makes it easier for the polymer to enter the bottom of the mold along the periphery of the large mold, and it is convenient for the small mold to be smoothly inserted into the large mold and the test piece to be completely taken out.

[0029] Before the preparation of the energy-absorbing metamaterial, the foam metal matrix is ​​acid-washed and alkaline-washed to remove impurities on the surface of the matrix; the mold release agent is applied to the inner surface of the large mold, and the sealable movable bottom is assembled and sealed with the large mold to prepare for filling; then the foam metal matrix is ​​placed in the center of the large mold to ensure that there are large gaps on all sides; the mixed polyurethane or epoxy resin is slowly poured along the gaps around the large mold to the bottom of the mold, and the polyurethane is shaken while pouring to ensure that the polyurethane is fully diffused from all sides to the center of the foam aluminum matrix; it should be noted that polyurethane and epoxy resin are alternately poured in layers, such as the first layer is poured with polyurethane, the second layer is poured with epoxy resin, and the third layer is poured with polyurethane, and so on.

[0030] When the pouring height reaches the preset height, the pouring is stopped. After the first layer is filled, it is cured at room temperature. If polyurethane is poured, the curing time is 3-10 minutes, preferably 5 minutes, to increase its viscosity to avoid interpenetration between the epoxy resin of the second layer and the polyurethane interface of this layer; then the mixed epoxy resin or polyurethane is slowly poured along the gaps around the large mold to the surface of the first pouring layer by the same means until the preset height is reached and the pouring is stopped. It is cured at room temperature. If epoxy resin is poured, the curing time is 5-15 min; when the number of poured layers is greater than 2 layers, continue to pour alternately until the last layer covers the upper surface of the foam metal substrate.

[0031] Apply the release agent evenly on the inner surface of the small mold and the surface of the gasket. After standing for 2 minutes, place the gasket on the upper surface of the specimen and align it with the upper surface of the specimen. Then, insert the small mold upside down into the bottom of the large mold so that it completely wraps the specimen, and invert the whole mold. Remove the movable bottom of the large mold, insert the demolding tool into the large mold from the bottom opening, and press the demolding tool down hard to ensure that the specimen is pressed into the bottom of the small mold. Take out the demolding tool and the large mold, clean the polymer adhered to the outer side of the small mold, put the small mold containing the specimen into a 50-70 ℃ constant temperature box for curing for 3-5 hours, and then demold it to obtain the energy-absorbing metamaterial.

[0032] It should be noted that the polyurethane used in the embodiment of the present invention is mixed by a first component and a second component, the first component includes: isocyanate; the second component includes: combined polyether; the epoxy resin is mixed by a third component and a fourth component, the third component includes: E44 epoxy resin glue; the fourth component includes: 650 epoxy curing agent; after the third component and the fourth component constituting the epoxy resin are mixed, they can be heated in a water bath at a temperature of 70-90°C for about 3-8 minutes to appropriately reduce the viscosity so that the polymer can be fully diffused from the surroundings to the center of the foam aluminum matrix; the foam metal matrix is ​​obtained by an infiltration casting process.

[0033] In a third aspect, the present invention provides an application of the orthotropic energy-absorbing metamaterial described in the first aspect, wherein the energy-absorbing metamaterial is used as a vertical force-bearing member, a horizontal force-bearing member, and a compressive web member in a building structure.

[0034] The energy-absorbing metamaterial provided by the present invention can be combined with concrete or steel structure and used as a vertical force-bearing member; by combining the orthotropic energy-absorbing metamaterial 101 with a traditional vertical structural member, such as a concrete member 102 and a steel structure member 103, an energy-absorbing metamaterial composite column (such as Fig.10 ), composite shear wall (such as Fig.11 ) and other composite structural components. Due to the introduction of this orthotropic energy-absorbing metamaterial, while effectively improving the bearing capacity and energy-absorbing capacity in the vertical direction, it also has a good energy-absorbing effect in the horizontal direction, playing a good role in impact protection. When the structural component is impacted, the compression deformation of the foam aluminum pore wall and the polymer, the friction and extrusion between the pore wall and different polymers, effectively absorbs a large amount of energy generated by the impact, greatly reduces the degree of damage to the structural component, and effectively ensures the safety of the main structure. Give full play to the energy absorption characteristics of this orthotropic energy-absorbing metamaterial in different directions.

[0035] The energy-absorbing metamaterial provided by the present invention can also be used as a horizontal force-bearing component, such as a vibration-isolating floor slab. By combining the orthotropic energy-absorbing metamaterial 101 with a steel plate component 1031 or a steel pipe component 1032, a composite vibration-isolating floor slab with both bearing capacity and energy absorption capacity is formed. Fig.12 , Fig.13 As shown, Fig.12 (a) is the axonometric view of the composite vibration isolation floor. Fig.12 (b) is the cross-sectional view of the composite vibration isolation floor; Fig.13 (a) is a schematic diagram of the structure of the orthotropic energy-absorbing metamaterial. Fig.13 (b) is a schematic diagram of a triangular steel tube structure; Fig.13 (c) is the axonometric view of the composite vibration isolation floor. Fig.13 (d) is a cross-sectional view of the composite vibration isolation floor slab. When the load acts on the composite floor slab, the composite floor slab has a higher compressive bearing capacity and vertical energy absorption capacity due to the high yield strength and energy absorption efficiency of the energy absorbing metamaterial in the vertical direction. At the same time, due to the high yield strength and elastic modulus of the energy absorbing metamaterial in the horizontal direction, when the floor slab is bent, Fig.12 The energy-absorbing metamaterial 101 core can bear higher horizontal tensile and compressive stresses and bending stiffness. Fig.13 The cores of the energy-absorbing metamaterial 101 in the horizontal direction squeeze each other, bear a high horizontal load and provide a large bending stiffness. Therefore, the composite floor has a high compressive strength and energy absorption capacity, and also has a high bending bearing capacity and bending stiffness. The energy absorption characteristics of the orthotropic energy-absorbing metamaterial in different directions are fully utilized.

[0036] The energy-absorbing metamaterial provided by the present invention can also be used as a compression web member in an arch bridge, and combined with a traditional compression web member in an arch bridge to form a composite structure compression web member with both axial bearing capacity and normal anti-collision energy absorption capacity. Fig.14 As shown, Fig.14 (a) shows the schematic diagram of the structure of the compressed web member of the composite structure. Fig.14 (b) shows a schematic diagram of the application of the composite structure compression web member in the bridge body; due to the introduction of the orthotropic energy-absorbing metamaterial 101, while effectively improving the bearing capacity and energy absorption capacity in the axial direction, it also has a good energy absorption effect in other directions, playing a good impact protection role. It can effectively absorb a large amount of energy generated by the impact, reduce the degree of damage to the composite structure compression web member 11, and thus effectively ensure the safety of the main structure.

[0037] In order to enable those skilled in the art to more clearly understand the present invention, the orthotropic energy absorbing metamaterial, preparation method and application of the present invention are now described in detail through the following embodiments.

[0038] Example 1 (1) Alkaline and acid wash the aluminum foam (AF) block, and then use alcohol to clean the mold, gasket, movable bottom and aluminum foam block respectively; after cleaning, seal the opening on the bottom surface of the large mold with the movable bottom to prevent polymer from seeping out, and evenly apply the release agent on the inner surface of the large mold; (2) Place an open-cell aluminum foam with a side length of 50 mm, a porosity of 66%, and a pore size distribution range of 9-11 mm in the center of the large mold, ensuring that there are large gaps on all sides; calculate the volume of polyurethane required to be filled in each layer (50 / 3 mm) based on the porosity of the aluminum foam and the size of the large mold, and then determine the mass of polyurethane required for each layer to be approximately 70 g based on the density of polyurethane; weigh 35 g of polyurethane A (isocyanate) and B (combined polyether) respectively, pour them into a container, mix and stir for about 30 seconds; slowly pour the mixed polyurethane along the gaps around the large mold to the bottom of the mold, shaking while pouring to ensure that the polyurethane is fully diffused from all sides to the center of the aluminum foam matrix; (3) After the first layer is filled, it is cured at room temperature for about 5 minutes. At the same time, 35g of epoxy resin A (E44 epoxy resin glue) and B (650 epoxy curing agent) are weighed respectively, mixed in a container and stirred for about 30 seconds, and heated in a water bath at 80°C for about 5 minutes; after heating in the water bath, it is stirred again for about 30 seconds, and the evenly stirred epoxy resin is slowly poured along the gaps around the large mold to the upper surface of the polyurethane layer, shaking while pouring to make it fully diffuse from the surroundings to the center of the foam aluminum matrix; (4) After the second layer is filled, cure it at room temperature for about 10 minutes. After curing, weigh 40g of polyurethane A and B respectively, pour them into a container and mix them for about 30 seconds. Pour the evenly stirred polyurethane directly from the upper surface of the specimen, shaking it while pouring, and stop pouring until the polyurethane completely covers the upper surface of the specimen. Pour the remaining polyurethane into the waste box. (5) Apply a release agent evenly on the inner surface of the small mold and the surface of the gasket. After standing for 2 minutes, place the gasket on the upper surface of the specimen and align it with the upper surface of the specimen; insert the small mold upside down into the bottom of the large mold so that it completely wraps the specimen, and turn the whole upside down; after removing the sealable movable bottom, insert the demoulder into the large mold from the upper hole, and press the demoulder down hard to ensure that the specimen is pressed into the bottom of the small mold; remove the demoulder and the large mold, and clean the polymer adhered to the outer side of the small mold; place the small mold containing the specimen in a 60°C constant temperature box for curing for 4 hours and then demould it, thereby obtaining the energy absorbing metamaterial (AF-UEU).

[0039] Embodiment 2: The foam aluminum alloy block is alkali-washed and pickled, and then the mold, gasket, movable bottom and foam aluminum block are cleaned with alcohol respectively; after cleaning, the movable bottom seals the opening on the bottom surface of the large mold to prevent polymer from seeping out, and at the same time, the mold release agent is evenly applied on the inner surface of the large mold; Place open-cell aluminum foam with a side length of 50 mm, a porosity of 66%, and a pore size distribution range of 9-11 mm in the center of the large mold, and ensure that there are large gaps on all sides; calculate the volume of epoxy resin required to be filled in each layer based on the porosity of the aluminum foam and the size of the large mold, and then determine the mass of epoxy resin required to be weighed for each layer based on the density of the epoxy resin, which is about 72 g; Weigh 36g of epoxy resin A (E44 epoxy resin glue) and B (650 epoxy curing agent) respectively, pour them into a container, stir for about 30s after mixing, place the stirred epoxy resin in a water bath pot at 80℃ for water bath heating for about 5min; after water bath heating, stir again for about 30s, slowly pour the stirred epoxy resin along the gaps around the large mold to the bottom of the mold, and shake while pouring to make it fully diffuse from the surroundings to the center of the foam aluminum matrix; After the first layer is filled, cure it at room temperature for about 10 minutes. After curing, weigh 36g of polyurethane material A (isocyanate) and material B (combined polyether), mix them in a container and stir for about 30 seconds. Slowly pour the evenly stirred polyurethane along the gaps around the large mold to the upper surface of the epoxy resin layer, shaking it while pouring, so that it can be fully diffused from the surroundings to the center of the foam aluminum matrix. After the second layer is filled, it is cured at room temperature for about 5 minutes. At the same time, 40g of epoxy resin A and B are weighed respectively, poured into a container for mixing, and the mixing time is about 30 seconds; the stirred epoxy resin is placed in a water bath pot at 80°C for water bath heating, and the heating time is about 5 minutes. After heating, it is stirred again for about 30 seconds; the evenly stirred epoxy resin is poured directly from the upper surface of the specimen, and it is shaken while pouring, and the pouring is stopped after the epoxy resin completely covers the upper surface of the specimen, and the remaining epoxy resin is poured into the waste box; Apply the release agent evenly on the inner surface of the small mold and the surface of the gasket. After standing for 2 minutes, place the gasket on the upper surface of the specimen and align it with the upper surface of the specimen; insert the small mold upside down into the bottom of the large mold so that it completely wraps the specimen, and turn the whole upside down; after removing the sealable movable bottom, insert the demoulder into the large mold from the upper hole, and press the demoulder down hard to ensure that the specimen is pressed into the bottom of the small mold; take out the demoulder and the large mold, and clean the polymer adhered to the outer side of the small mold; put the small mold containing the specimen into a 60°C constant temperature box for curing for 4 hours and then demould it, thereby obtaining the energy absorbing metamaterial (AF-EUE).

[0040] Comparative Example 1 The difference from Example 1 is that the open holes of the foamed aluminum (AF) are filled with polyurethane to obtain the energy absorbing material (AF-PU).

[0041] Comparative Example 2 The difference from Example 1 is that the openings of the foamed aluminum (AF) are filled with epoxy resin to obtain the energy absorbing material (AF-EP).

[0042] Figure 6 FIG. 4 shows a physical picture of an orthotropic energy absorbing metamaterial provided by an embodiment of the present invention, such as Figure 6 As shown, AF-EUE1 and AF-EUE2 are physical pictures of the orthotropic energy-absorbing metamaterials prepared in Example 1, and the difference between AF-EUE1 and AF-EUE2 is that the polymer filling directions therein are perpendicular to each other. AF-UEU1 and AF-UEU2 are physical pictures of the orthotropic energy-absorbing metamaterials prepared in Example 2, and the difference between AF-UEU1 and AF-UEU2 is that the polymer filling directions therein are perpendicular to each other.

[0043] Figure 7 The stress-strain curves of different energy absorbing materials after averaging in the present invention are shown as follows: Figure 7 As shown. As can be seen from the figure, AF-PU has good plastic properties and a smooth plastic platform segment. Compared with AF, AF-PU has a longer plastic platform segment and a higher yield strength. AF-EP has obvious brittle characteristics. Although it has high yield strength and elastic modulus, it has no obvious plastic platform segment, and has an obvious descending segment after the compressive strain exceeds 0.4, showing brittle failure. The orthotropic energy-absorbing metamaterial not only retains the good plastic development ability of AF-PU, but also has high-strength characteristics similar to AF-EP. Their yield strengths are from large to small: AF-EUE2>AF-EUE1>AF-UEU2>AF-UEU1. That is: for the two energy-absorbing metamaterials of the present invention, the yield strength: AF-EUE>AF-UEU, and each energy-absorbing metamaterial has a vertical yield strength greater than the horizontal yield strength.

[0044] Figure 8 FIG. 4 shows a comparison diagram of the ideal energy absorption efficiency of different energy absorption materials in the present invention; Figure 8As shown in the figure, it can be seen that the ideal energy absorption efficiency curve of each energy absorbing material has three-stage characteristics of an ascending section, a platform section and a descending section. In the initial ascending stage of the curve, it can be seen that the ideal energy absorption efficiency of the orthotropic energy absorbing metamaterial is close to that of the traditional foam aluminum-polymer energy absorbing material. When the curve enters the platform section, the orthotropic energy absorbing metamaterial has an ideal energy absorption efficiency significantly higher than that of AF and AF-EP. The orthotropic energy absorbing metamaterial has a longer and smoother ideal energy absorption efficiency platform section while having a high ideal energy absorption efficiency close to that of AF-PU. In particular, AF-UEU2 can maintain a high ideal energy absorption efficiency close to 0.85 within a wide strain range of 0.12-0.6, and is an orthotropic energy absorbing metamaterial that is very close to the ideal energy absorbing material.

[0045] Fig. 9 The energy absorption index comparison diagram of different energy absorbing materials in the present invention is shown; it can be seen from the figure that compared with AF-PU, the orthotropic anisotropic energy absorbing metamaterial and The energy absorption values ​​of some energy-absorbing metamaterials are even close to that of AF-EP. The values ​​have also increased, most of which have exceeded 0.5, among which AF-UEU2 The value is as high as 0.645, which means that the orthotropic energy-absorbing metamaterial has better plastic development ability. Therefore, the orthotropic energy-absorbing metamaterial has both good plasticity that exceeds AF-PU and high platform stress and energy absorption close to AF-EP. In addition, through comparison, it is found that the energy absorption index of the orthotropic energy-absorbing metamaterial in different orthogonal directions has different sizes, and each direction has its own energy absorption characteristics, which can more widely meet the needs of practical engineering.

[0046] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.

[0047] For the method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and components involved are not necessarily required by the present invention.

[0048] The orthotropic energy-absorbing metamaterial, preparation method and application provided by the present invention are introduced in detail above. The principle and implementation mode of the present invention are explained in detail using specific examples herein. The description of the above embodiments is only used to help understand the method and core idea of ​​the present invention. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. An orthotropic energy-absorbing metamaterial, characterized in that: The energy-absorbing metamaterial is composed of an open-pored foam metal matrix, and polyurethane and epoxy resin filled in the cell cavities inside the foam metal matrix; wherein the polyurethane and epoxy resin are alternately layered and filled in the cell cavities inside the foam metal matrix.

2. The orthotropic energy absorbing metamaterial according to claim 1, characterized in that: The porosity of the foam metal matrix is ​​45-75%, and the pore size of the cell cavity is 5-15 mm.

3. The orthotropic energy absorbing metamaterial according to claim 1, characterized in that: The single-layer filling height of the polyurethane is the same as the single-layer filling height of the epoxy resin.

4. The orthotropic energy absorbing metamaterial according to claim 1, characterized in that: The polyurethane and epoxy resin are alternately layered and filled in the cell cavity inside the foam metal matrix, including: the polyurethane is filled in the odd-numbered layers, and the epoxy resin is filled in the even-numbered layers; or the polyurethane is filled in the even-numbered layers, and the epoxy resin is filled in the odd-numbered layers.

5. The orthotropic energy absorbing metamaterial according to claim 1, characterized in that: The foam metal matrix is ​​a foam aluminum matrix, a foam aluminum alloy matrix or a foam titanium matrix.

6. A method for preparing the orthotropic energy-absorbing metamaterial according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Step 1: placing the foam metal matrix at the center of a large mold with a sealable movable bottom; Step 2, slowly pouring polyurethane or epoxy resin along the gaps around the large mold to the bottom of the mold, and allowing the polyurethane or epoxy resin to fully enter the cell cavity inside the foam metal matrix, and stopping the pouring when the pouring reaches a first predetermined height, and initially solidifying to form a first pouring layer; Step 3, slowly pouring epoxy resin or polyurethane along the gaps around the large mold onto the surface of the first pouring layer, and allowing the epoxy resin or polyurethane to fully enter the cell cavity inside the foam metal matrix, and stopping the pouring when the pouring reaches a second predetermined height, and initially solidifying to form a second pouring layer; Step 4, repeating steps 2 and 3 until the total height of the pouring is consistent with the height of the foam metal matrix, then stopping the pouring and standing to solidify for 1-2 hours; Step 5, inserting the small mold with a movable bottom into the large mold upside down, and making the small mold completely wrap the foam metal matrix, after the whole is inverted, removing the movable bottom of the large mold, and using a demolding tool to press the foam metal matrix into the bottom of the small mold to separate it from the large mold; Step 6: Place the separated small mold in a 50-70° C. constant temperature box for curing for 3-5 hours and then demould to obtain the orthotropic energy-absorbing metamaterial.

7. The method for preparing the orthotropic energy absorbing metamaterial according to claim 6, characterized in that: The polyurethane is formed by mixing a first component and a second component, wherein the first component includes: isocyanate; The second component includes: a combined polyether; The curing time required for the pouring layer formed by pouring polyurethane is 3-10 minutes.

8. The method for preparing the orthotropic energy absorbing metamaterial according to claim 6, characterized in that: The epoxy resin is mixed by a third component and a fourth component, and the third component includes: E44 epoxy resin glue; The fourth component includes: 650 epoxy curing agent; The curing time required for the pouring layer formed by pouring epoxy resin is 5-15 minutes.

9. The method for preparing the orthotropic energy absorbing metamaterial according to claim 6, characterized in that: The foam metal substrate is firstly subjected to alkali washing and acid washing before use; Before use, the large mold and the small mold are evenly coated with a release agent on the inner surface.

10. An application of the orthotropic energy absorbing metamaterial according to any one of claims 1 to 5, characterized in that: The energy-absorbing metamaterial is used in building structures as vertical force-bearing components, horizontal force-bearing components and compression web members.